ANALYSIS OF FARMERS DECISION TO PARTNER WITH ARA CAHAYANI GAYO COFFEE COOPERATIVE IN BANDAR DISTRICT, BENER MERIAH REGENCY - Siti Salmah; Zuriani Zuriani; Martina Martina (LPPM Universitas Malikussaleh - Indonesia, 2024)
This research was conducted in Ara Cahayani Gayo Cooperative in Bandar District. Ara Cahayani Gayo Cooperative is a cooperative that has the largest number of members in Bandar District. Of the 2.753 members who joined Ara Cahayani Gayo, only 456 members came from Bandar district, while the rest mostly came from other districts. This shows that there are still few farmers in the District of Bandar who joined Ara Cahayani Gayo. This study aims to analyze the factors that influence farmers' decisions to partner with Ara Cahayani Gayo coffee cooperatives in Bandar District, Bener Meriah Regency. The data analysis method used in this research is descriptive quantitative and qualitative with binary logistic regression. Sampling using simple random sampling with a total of 46 partner farmers and 48 non-partner farmers. The results showed that of the 5 independent variables included in the model, there are 4 independent variables that have a significant effect on the decision of farmers partnering with Ara Cahayani Gayo, namely the land area with a significant value of 0.002, the number of family members with a significant value of 0.043, market assurance with a significant value of 0.001 and training with a significant value of 0.003. While 1 other variable, namely experience with a significant value of 0.124, has no significant effect on the decision of farmers to partner with the Ara Cahayani Gayo cooperative.Keywords: partnership, farmer decisions, coffee cooperative